The IASP classification of chronic pain for ICD-11 - chronic postsurgical or posttraumatic pain - Schug, Stephan A.; Lavand'homme, Patricia; Barke, Antonia; Korwisi, Beatrice; Rief, Winfried; Treede, Rolf-Detlef (Pain, 2019)
Abstract: Chronic pain after tissue trauma is frequent and may have a lasting impact on the functioning and quality of life of the affected person. Despite this, chronic postsurgical and posttraumatic pain is underrecognised and, consequently, undertreated. It is not represented in the current Interna
Gesehen am 25.06.2019